Three‐dimensional Integrated Functional, Structural, and Computational Mapping to Define the Structural "Fingerprints" of Heart‐Specific Atrial Fibrillation Drivers in Human Heart Ex Vivo. Issue 8 (August 2017) - Zhao, Jichao; Hansen, Brian J.; Wang, Yufeng; Csepe, Thomas A.; Sul, Lidiya V.; Tang, Alan; Yuan, Yiming; Li, Ning; Bratasz, Anna; Powell, Kimerly A.; Kilic, Ahmet; Mohler, Peter J.; et al.
Abstract : Background: Structural remodeling of human atria plays a key role in sustaining atrial fibrillation (AF), but insufficient quantitative analysis of human atrial structure impedes the treatment of AF. We aimed to develop a novel 3‐dimensional (3D) structural and computational simulation analysis tool that could reveal the structural contributors to human reentrant AF drivers. Methods and Results: High‐resolution panoramic epicardial optical mapping of the coronary‐perfused explanted intact human atria (63‐year‐old woman, chronic hypertension, heart weight 608 g) was conducted during sinus rhythm and sustained AF maintained by spatially stable reentrant AF drivers in the left and right atrium. The whole atria (107×61×85 mm 3 ) were then imaged with contrast‐enhancement MRI (9.4 T, 180×180×360‐μm 3 resolution). The entire 3D human atria were analyzed for wall thickness (0.4–11.7 mm), myofiber orientations, and transmural fibrosis (36.9% subendocardium; 14.2% midwall; 3.4% subepicardium). The 3D computational analysis revealed that a specific combination of wall thickness and fibrosis ranges were primarily present in the optically defined AF driver regions versus nondriver tissue. Finally, a 3D human heart–specific atrial computer model was developed by integrating 3D structural and functional mapping data to test AF induction, maintenance, and ablation strategies. This 3D model reproduced the optically defined reentrant AF drivers, which were uninducible when fibrosis and myofiber anisotropy were removed from the model. Conclusions: Our novel 3D computational high‐resolution framework may be used to quantitatively analyze structural substrates, such as wall thickness, myofiber orientation, and fibrosis, underlying localized AF drivers, and aid the development of new patient‐specific treatments.